2015
DOI: 10.1007/s11914-015-0279-7
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and the Common Mental Disorders: a Potential Regulatory Role of Skeletal Muscle on Brain Function?

Abstract: While it is understood that body composition impacts on physical conditions, such as diabetes and cardiovascular disease, it is only now apparent that body composition might play a role in the genesis of common mental disorders, depression and anxiety. Sarcopenia occurs in ageing and comprises a progressive decline in muscle mass, strength and function, leading to frailty, decreased independence and poorer quality of life. This review presents an emerging body of evidence to support the hypothesis that shared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 101 publications
(83 reference statements)
0
59
0
Order By: Relevance
“…Physical exercise enhances circulating BDNF, down-regulates systemic inflammation and is recognized as an effective treatment for depression and anxiety. Antidepressant treatment normalizes markers of inflammation and oxidative stress [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Physical exercise enhances circulating BDNF, down-regulates systemic inflammation and is recognized as an effective treatment for depression and anxiety. Antidepressant treatment normalizes markers of inflammation and oxidative stress [39]. …”
Section: Discussionmentioning
confidence: 99%
“…35 Currently, the association between obesity and depression as well as between metabolic syndrome and depression has been confirmed by meta-analytic studies. 38 As decreased neurotrophic support of the brain has been associated with depression and anxiety, 41,42 sarcopenia may pose a vulnerability for these common mental disorders. These inconsistencies may be explained by the fact that none of these studies specifically addressed sarcopenic obesity.…”
Section: Sarcopenic Obesity As a Potential Risk Factor For Depressionmentioning
confidence: 99%
“…Sarcopenia rates vary widely in obese patients depending on the criteria used. 38 An increased proinflammatory state promotes insulin resistance by an increased level of circulating free fatty acids and glycerol. Recently, it has been hypothesized that contracting skeletal muscles contribute to brain preservation by the secretion of neurotrophic factors.…”
Section: Sarcopenic Obesity As a Potential Risk Factor For Depressionmentioning
confidence: 99%
“…Impairment of lower extremity performance and activities of daily living impairment have also been found to be both risk factors for or consequences to depression (1517), frequently leading to sedentary behavior (18) and functional dependence among older persons (16). Most recently, an accumulation of evidence has suggested that diagnoses of sarcopenia and sarcopenia with obesity are associated with depression (1922). However, large dataset studies have also reported findings on no associations between sarcopenia and depression (23, 24).…”
Section: Introductionmentioning
confidence: 99%